Response to Bock and Coward - Dourley, John P. (The international journal for the psychology of religion, 1995)
Jung's thought does, indeed, contain a metaphysics, even though he claimed he was an empiricist. He would argue that God necessarily creates the psyche in order to become conscious in it. But all reality is, thereby, psychic and thus, incompatible with monotheism. Jung moves from a trinitarian to a quaternitarian position because he felt that traditional dogma missed the bodily, the demonic, and the feminine. He felt that conventional religion militated against the internal dialogue that he felt was necessary to true faith. To bypass this essential psychological process by reference to a transcendent divinity who evokes a moral consciousness is inappropriate.